Genome-wide identification and diversity of FAD2, FAD3 and FAE1 genes in terms of biotechnological importance in Camelina species - Rostyslav Y. Blume; Vitaliy Y. Hotsuliak; Tara J. Nazarenus; Edgar B. Cahoon; Yaroslav B. Blume (BMC Biotechnology)
Abstract Background False flax, or gold-of-pleasure (Camelina sativa) is an oilseed that has received renewed research interest as a promising vegetable oil feedstock for liquid biofuel production and other non-food uses. This species has also emerged as a model for oilseed biotechnology research that aims to enhance seed oil content and fatty acid quality. To date, a number of genetic engineering and gene editing studies on C. sativa have been reported. Among the most common targets for this research are genes, encoding fatty acid desaturases, elongases, and diacylglycerol acyltransferases. However, the majority of these genes in C. sativa are present in multiple copies due to the allohexaploid nature of the species. Therefore, genetic manipulations require a comprehensive understanding of the diversity of such gene targets. Results Here we report the detailed analysis of FAD2, FAD3 and FAE1 gene diversity in five Camelina species, including hexaploid C. sativa and four diploids, namely C. neglecta, C. laxa, C. hispida var. hispida and var. grandiflora. It was established that FAD2, FAD3 and FAE1 homeologs in C. sativa retain very high conservancy, despite their allohexaploid inheritance. High sequence conservancy of the identified genes along with their different expression patterns in C. sativa suggest that subfunctionalization of these homeologs is mainly grounded on the transcriptional balancing between subgenomes. Finally, fatty acid composition of seed lipids in different Camelina species was characterized, suggesting potential variability in the activity of fatty acid elongation/desaturation pathways may vary among these taxa. Conclusion It was shown that the FAD2, FAD3 and FAE1 genes retain high conservation, even in allohexaploid C. sativa after polyploidzation, in which the subfunctionalization of the described homeologs is mainly grounded on the expressional differences. The major differences in FA accumulation patterns within the seeds of different species were identified as well. These results provide a foundation for future precise gene editing, which would be based on targeting of particular FAD2, FAD3 and FAE1 gene copies in C. sativa that allow regulating the dosage of the mentioned genes, thus shaping the desired FA composition in cultivated false flax.